New Orleans’ school meals distribution in response to the COVID-19 pandemic: operational details and geographic coverage - Chaparro, M. Pia; French, Jacob; Creveling, Kristine; Ennin, Naana; Numa, Tiffany; Knapp, Megan (Frontiers in Public Health, 2023)
Introduction To facilitate continuation of school feeding during COVID-19 school lockdowns, U.S. Congress authorized waivers to allow for school meals to be picked up by parents/guardians in non-school settings. We summarized school meals distribution and characterized reach in socially vulnerable neighborhoods in New Orleans, a city prone to environmental disasters, with a city-wide charter school system, and historically high levels of child poverty and food insecurity. Methods School meals operations data were obtained from New Orleans, Louisiana (NOLA) Public Schools for 3/16/2020–5/31/2020. For each pick-up location, we estimated: average meals available (weekly), average meals served (weekly), number of weeks of operation, and rate of meal pick-up ([meals served/meals available]*100). These characteristics were mapped in QGIS v3.28.3, along with neighborhoods’ Social Vulnerability Index (SVI). Pearson correlation and ANOVA were run to assess differences between operations characteristics and neighborhood SVI. Results From 38 meal sites, 884,929 meals were available for pick-up; 74% of pick-up sites were in moderately/highly socially vulnerable areas. Correlations between average meals available and served, weeks of operation, rate of meal pick-up, and SVI were weak and not statistically significant. SVI was associated with average rate of meal pick-up but not other operations characteristics. Discussion Despite the disaggregated nature of the charter school system, NOLA Public Schools successfully pivoted to providing children with pick-up meals due to COVID-19 lockdowns, with 74% of sites located in socially vulnerable neighborhoods. Future studies should describe the types of meals provided to students during COVID-19, in terms of diet quality and nutrient adequacy.